Deposit Insurance in the Republic of Macedonia - Zoran Jovanovski (National Bank of the Republic of Macedonia, 1998)
Additional protection of the stability of the banking system and deposited funds in the banks and savings houses is provided by the systems for deposit insurance (implicit or explicit). Wolrdwide, particularly in the developing countries and economies in transition, there is a tendency to introduce explicit systems, because they are considered to have the following advantages: 1/ they have better administrative procedure for dealing with banks'bankruptcies and depositors protection; 2/ they are more efficient in protecting the "small depositors", because at least partial compensation is guaranteed to them in a case of a risky event, and 3/ they contribute to a larger extent in improving the establishing and maintaining public confidence in the country's banking system. With a Directive from 1994 the European Union also urged to its member countries to introduce explicit deposit insurance schemes. In the Republic of Macedonia there is a Savings Insurance Fund, as an explicit system for savings protection, established as a shareholding company by the banks and savings houses. The Fund regularly collects the insurance premiums, but points out some problems in its operations, like the lack of independence in the decision making, insufficient information, and limited scope of activities. The Fund has a specific character and should not function as a classic shareholding company, because of the: 1/ basic objective of its functioning; 2/ current regulation requiring mandatory membership in the Fund; 3/ needs of the Fund for more information on the activities of the members being not satisfied; 4/ unsustainability of duality in executing the supervision function, and 5/ elimination of the possibility for the Fund's shares to be traded on the Macedonian stock exchange.
Keywords: 330; Einlagensicherung; Mazedonien